Biological Effect of Exract of Cryopreserved Piglet’s Heart Fragments in Ischemia and Spontaneous Myocardial Infarction - Rohoza, Liliia A. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):167.